Nuclear Export and Centrosome Targeting of the Protein Phosphatase 2A Subunit B56α: ROLE OF B56α IN NUCLEAR EXPORT OF THE CATALYTIC SUBUNIT - Flegg, Cameron P; Sharma, Manisha; Medina-Palazon, Cahora; Jamieson, Cara; Galea, Melanie; Brocardo, Mariana G; Mills, Kate; Henderson, Beric R (The Journal of biological chemistry, 2010)
Protein phosphatase (PP) 2A is a heterotrimeric enzyme regulated by specific subunits. The B56 (or B'/PR61/PPP2R5) class of B-subunits direct PP2A or its substrates to different cellular locations, and the B56α, -β, and -ε isoforms are known to localize primarily in the cytoplasm. Here we studied the pathways that regulate B56α subcellular localization. We detected B56α in the cytoplasm and nucleus, and at the nuclear envelope and centrosomes, and show that cytoplasmic localization is dependent on CRM1-mediated nuclear export. The inactivation of CRM1 by leptomycin B or by siRNA knockdown caused nuclear accumulation of ectopic and endogenous B56α. Conversely, CRM1 overexpression shifted B56α to the cytoplasm. We identified a functional nuclear export signal at the C terminus (NES; amino acids 451-469), and site-directed mutagenesis of the NES (L461A) caused nuclear retention of full-length B56α. Active NESs were identified at similar positions in the cytoplasmic B56-β and ε isoforms, but not in the nuclear-localized B56-δ or γ isoforms. The transient expression of B56α induced nuclear export of the PP2A catalytic (C) subunit, and this was blocked by the L461A NES mutation. In addition, B56α co-located with the PP2A active (A) subunit at centrosomes, and its centrosome targeting involved sequences that bind to the A-subunit. Fluorescence Recovery after Photobleaching (FRAP) assays revealed dynamic and immobile pools of B56α-GFP, which was rapidly exported from the nucleus and subject to retention at centrosomes. We propose that B56α can act as a PP2A C-subunit chaperone and regulates PP2A activity at diverse subcellular locations.